Effect of Perceived Value on Satisfaction to Microtransactions in Valorant - Khairul Arifin; M. Rheza Agung S; Veneishia Gricelda; Rano Kartono (Green Publisher Indonesia, 2023)
Current technological developments, especially in the digital game industry, have built new business opportunities in a digital game and caused a new phenomenon that is linked to Microtransaction, which is also found in the Valorant game. There are pros and cons of using microtransactions, as well as limited research on Valorant games, especially those related to the variables of emotional value, social value, functional value, value for money (good price), satisfaction, and purchase intention of the game, so this study aims to examine more deeply about consumer motivation from perceived value to satisfaction to purchase intention, especially in the Valorant game. A total of 333 respondents in the Jabodetabek area have been studied using purposive sampling techniques. This study used Smart PLS 3.0 to test the validity, reliability, and results of the hypotheses. This study looked at the relationship between perceived value to satisfaction and satisfaction with purchase intention, especially in Valorant games. The results of the study stated that social value, functional value, and value for money have an effect on satisfaction, as well as satisfaction affects purchase intention. Meanwhile, emotional value has no influence on satisfaction.